Vein Visualization With a Near Infrared Imaging Device and Its Impact on Students' and Nurses' Skills in an Academic Teaching University Hospital - Renno, Isabell; Horch, Raymund E.; Ludolph, Ingo; Cai, Aijia; Arkudas, Andreas (Journal of Infusion Nursing, 2024)
Venipuncture for blood collection is frequently delegated to medical or nursing students, while their individual skills depend on the quality of teaching. The aim of this study was to evaluate the use of a near infrared imaging (NIR) system on the visualization of veins and its potential benefit for the education of medical personnel. Participants answered a questionnaire following standardized venipuncture for blood sampling with the help of an NIR device. Vein visibility with the NIR device and its ability to facilitate venipuncture were examined. Visibility of veins was significantly better with the NIR, and its direction was clearly delineated. Sixty-nine percent of the participants stated that they felt more secure with venipuncture after using the NIR device. Patients' individual factors limited the visibility of veins. The adjuvant use of an NIR system for venipuncture improves participants' subjective skills through visualization of veins and their direction.
CRIS-Team Scopus Importer:2024-07-19